Comparison of body fat percentage of male soccer players of different competitive levels, playing positions and age groups: a meta-analysis - Slimani, M.; Znazen, H.; Hammami, A.; Bragazzi, N. L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the present meta-analysis was to compare the body fat percentage (%) between male soccer players of different competitive levels, playing positions and age groups. EVIDENCE ACQUISITION: The systematic search was conducted using different databases and according to the Population/Intervention or Exposure/Comparison/Outcome(s) [PICO] criteria. EVIDENCE SYNTHESIS: Higher percentage values of body fat in lower-level soccer players than higher-level counterparts (ES=0.18, 95% CI -0.86 to -0.14, P=0.006) were noted. Higher body fat % values in goalkeepers than defenders (ES=0.21, 95% CI -1.17 to -0.34, P<0.001), midfielders (ES=0.26, 95% CI -1.50 to -0.45, P<0.001) and forwards (ES=0.18, 95% CI -1.26 to -0.53, P<0.001) were observed. There was no significant association between % of body fat and age (P=0.86). CONCLUSIONS: In conclusion, body fat percentage clearly distinguished higher- from lower-level soccer players. These findings also imply that body fat percentage differ as a function of positional role in soccer and that sports scientists, coaches, and strength and conditioning professionals need to be aware of the specific positional requirements in soccer in terms of body fat. However, due to some limitations of the present meta-analysis (high statistically significant heterogeneity and evidence of publication bias), further studies are urgently needed in the field.